STRATEGI KONTEN TIM CONTENT CREATOR PADA PEMBUATAN KONTEN VIDEO TIKTOK BRAND 5DAYS SAVORIA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the content strategies implemented by the content creator team in producing TikTok video content for the 5Days brand of Savoria. Using a qualitative descriptive approach, the research explores the workflow covering pre-production, production, and post-production stages. Particular attention is given to the application of the AIDA (Attention, Interest, Desire, Action) model as the core framework guiding message delivery, visual direction, and audience engagement. Data were collected through interviews, direct observation, active participation, and literature review. The findings show that the integration of AIDA in content planning enhances message clarity, strengthens emotional resonance, and increases audience interaction with the brand’s TikTok content. The study also reveals that systematic coordination between the digital marketing team and content creators ensures consistency, creativity, and alignment with brand communication goals. Overall, the implementation of structured content strategies effectively supports brand visibility and enriches the audience experience on TikTok.